Enhancing extinction learning: Occasional presentations of the unconditioned stimulus during extinction eliminate spontaneous recovery, but not necessarily reacquisition of fear - Thompson, A.; McEvoy, P.; Lipp, Ottmar (Elsevier, 2018)
Background: Fears underlying anxiety disorders are commonly treated with exposure-based therapies, which are based on the principles of extinction learning. While these treatments are efficacious, fears may return after successful treatment. Past research suggested that post-extinction recovery of fear could be reduced through extinction training that involves occasional presentations of the aversive unconditioned stimulus (US), paired with the conditioned stimulus (CS). Here, we examined whether extinction training with occasionally paired or unpaired US presentations is superior in the reduction of fear recovery to non-reinforced extinction. Method: Following differential fear conditioning to neutral cues, participants (N = 72; M age = 21.61 years, SD = 3.95) underwent either non-reinforced, partially reinforced, or unpaired extinction training. Results: Extinction involving paired or unpaired US presentations, but not non-reinforced extinction, eliminated spontaneous recovery of differential skin conductance responses (SCRs). Results further suggested that unpaired, but not paired, US presentations may guard against rapid reacquisition of differential SCRs. No benefits of US presentations during extinction were found on the reinstatement of SCRs or recovery of differential negative CS+ valence. Conclusion: Presenting USs during extinction training was more effective than non-reinforced extinction in the reduction of fear recovery, as indexed by SCRs, with unpaired extinction being more effective than partially reinforced extinction.